Adaptation and cross-cultural validation of the Brazilian version of the Warwick-Edinburgh mental well-being scale - Santos,Jefferson Jovelino Amaral dos (2015)
Summary Objective: the Warwick-Edinburgh mental well-being scale (WEMWBS) was designed to assess the level of mental well-being of a population or specific groups. The scale consists of 14 items covering functional psychological aspects, as well as well-being. The final score is calculated by adding up the response of each item, ranging from 1 to 5, obtaining a result from 14 to 70 points. Methods: the procedure was developed in accordance with the protocol recommended by the World Health Organization covering translation, back translation, semantic equivalence, expert evaluation of the previous steps, pre-test and final version of the instrument. Following, the final version was applied to a sample of 122 individuals and the data were subjected to descriptive statistical analysis, factor analysis, internal consistency and correlation with other validated instruments. Results: we performed the instrument's adaptation to the Portuguese spoken in Brazil, replacing terms to approximate the language to expressions of everyday life. The final version showed similar results to those from the original version, demonstrated by factor analysis, internal consistency (Cronbach's alpha: 0.89) and positive correlation with instruments validated to the Portuguese language. Conclusion: the Brazilian version of the WEMWBS proved to be easy to use and understand, showed high internal consistency and construct validity similar to the original instrument.